Antiproliferative and genotoxic potential from extracts and fractions of Richardia brasiliensis Gomes (Rubiaceae) by the Allium cepa L. test system - Dornelles, Rafaela C.; Leal, Gabriela C.; Decian, Ana Carla S.; Santos, Daniele D. dos; Radiske, Gabriel A.; Manfron, Melânia P.; Tedesco, Solange B. (Iheringia, Série Botânica., 2018)
The medicinal species Richardia brasiliensis Gomes has secondary metabolites with considerable pharmacological activities. This study aims to determine the antiproliferative and genotoxic capacity of extracts and fractions obtained from the aerial parts of R. brasiliensis, in the Allium cepa test, on which one can detect the damages on chromosomes and the infl uence on cell proliferation during the mitotic cycle. The antiproliferative and genotoxic eff ect from extracts and fractions were evaluated at concentrations of 10 and 500 µg/mL and the mitotic index (MI) and the percentage of chromosomal alterations (CA) were calculated and used on the χ² test. It was observed antiproliferative capacity, the best results were from the autumn crude extract, and the hexane and butanol fractions with lower MI than the negative control. All treatments were genotoxic with CA, but with lower values than the ones found in the positive control.